2022
DOI: 10.1101/2022.03.08.483548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introducing RELAX (the Reduction of Electroencephalographic Artifacts): A fully automated pre-processing pipeline for cleaning EEG data - Part 1: Algorithm and Application to Oscillations

Abstract: Electroencephalographic (EEG) data is typically contaminated with non-neural artifacts which can confound the results of experiments. Artifact cleaning approaches are available, but often require time-consuming manual input and significant expertise. Advancements in artifact cleaning often only address a single artifact, are only compared against a small selection of pre-existing methods, and seldom assess whether a proposed advancement improves experimental outcomes. To address these issues, we developed RELA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 71 publications
(60 reference statements)
1
40
0
Order By: Relevance
“…In the present study, only the eyes-closed data were analysed so as to reduce the occurrence of electrooculography artifacts in the EEG record, as well as to remain consistent with Aykan et al [7] who also reported results obtained from eyes-closed resting-state data. The EEG data were pre-processed in MATLAB (R2020a, The Mathworks, Massachusetts, USA) using an automated cleaning pipeline (Reduction of Electrophysiological Artifacts [RELAX]) [16]. For further details on data pre-processing see [17].…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, only the eyes-closed data were analysed so as to reduce the occurrence of electrooculography artifacts in the EEG record, as well as to remain consistent with Aykan et al [7] who also reported results obtained from eyes-closed resting-state data. The EEG data were pre-processed in MATLAB (R2020a, The Mathworks, Massachusetts, USA) using an automated cleaning pipeline (Reduction of Electrophysiological Artifacts [RELAX]) [16]. For further details on data pre-processing see [17].…”
Section: Methodsmentioning
confidence: 99%
“…Epochs with voltages exceeding +/-60 μV at any electrode were rejected, as were epochs containing improbable voltage distributions or kurtosis values >5SD from the mean in any single electrode or more than 3SD from the mean over all electrodes. Data were then baseline corrected by regressing out the average of the -400 to -100ms period from each epoch (timelocked to the response) using the fieldtrip function 'ft_regressconfounds' for each electrode and each participant separately, with the condition of each epoch (correct or error response) included in the regression model (but not rejected) to correct for potential voltage drift but still preserve any experimental effects (Bailey et al, 2022a(Bailey et al, , 2022b.…”
Section: Statisticsmentioning
confidence: 99%
“…To address these issues, we built the “RELAX” EEG cleaning pipeline (short for “Reduction of Electroencephalographic Artifacts”), in which we combined and adjusted pre-existing approaches to optimise EEG cleaning and ERP outcomes. The pipeline is explained in detail in our companion article (Bailey et al, 2022), but in brief, RELAX: 1) Removes bad electrodes and extreme outlying EEG periods that are unlikely to have recorded meaningful or recoverable brain activity using a combination of algorithms obtained from previous research so that the rejected data matched our expert judgement for all common extreme artifact types; 2) The pipeline then reduces artifacts with Multi-channel Wiener Filters (MWF) (Borowicz, 2018; Somers et al, 2018); and 3) RELAX further reduces any remaining artifacts using wavelet enhanced ICA (wICA) (Castellanos & Makarov, 2006) applied to artifact components identified by the machine learning algorithm ‘ICLabel’ (Pion-Tonachini et al, 2019). This combination approach effectively cleans blinks, muscle activity, horizontal eye movement, voltage drift, and atypical artifacts to produce more dependable ERP estimates that indicate increased signal-to-noise ratios.…”
Section: Introductionmentioning
confidence: 99%
“…A condition of use of the pipeline is that the version of the pipeline used is referred to as RELAX_[pipeline], for example "RELAX_MWF_wICA" or "RELAX_wICA_ICLabel", and that the current paper be cited, as well as the dependencies used. These dependencies are likely to include: EEGLAB (Delorme & Makeig, 2004), fieldtrip (Oostenveld et al, 2011), the MWF toolbox (Somers et al, 2019), fastICA (Hyvarinen, 1999), wICA (Castellanos & Makarov, 2006), ICLabel (Pion-Tonachini et al, 2019), and PREP (Bigdely-Shamlo et al, 2015) See our companion article for the application of RELAX to the study of oscillatory power (Bailey et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation